On solution mapping and remeshing in crystal plasticity finite element simulations: application to equal channel angular pressing - Frydrych, Karol; Kowalczyk-Gajewska, Katarzyna; Prakash, Aruna (Modelling and Simulation in Materials Science and Engineering, 2019)
Microstructure evolution in crystalline materials subjected to different loading conditions is regularly studied using crystal plasticity finite element simulations. Accurate and reliable description of the microstructure, particularly in the case of large deformations, requires the usage of remeshing procedures and the mapping of the material state from the distorted mesh onto a new mesh. In this work, we evaluate three different solution mapping schemes, viz. closest point projection (CPP), sequential spherical linear interpolation (SLERP), and weighted spherical averages, all of which are based on the mapping of crystal plasticity variables. The results show that the mapping with CPP is generally acceptable, whilst the sequential SLERP is a more robust method with little additional computing effort.
CRIS-Team WoS Importer:2019-07-23